2011
DOI: 10.1007/s11426-010-4202-x
|View full text |Cite
|
Sign up to set email alerts
|

Micellization of copolymers via noncovalent interaction with TPPS and aggregation of TPPS

Abstract: Aggregation of 5,10,15,20-tetrakis-(4-sulfonatophenyl)-porphyrin (TPPS) was investigated in complex micelles composed of poly(ethylene glycol)-block-poly(4-vinylpyridine) (PEG-b-P4VP) and poly(2-(dimethylamino)ethyl methylacrylate)-b-poly(Nisopropylacrylamide) (PDMAEMA-b-PNIPAM) in aqueous solutions. The resultant complex micelles had a complex P4VP/ PDMAEMA/TPPS core and a mixed PEG/PNIPAM shell. Different noncovalent interaction modes between the porphyrin and each copolymer accomplished a co-effect on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…From this phenomenon, it can be inferred that H-aggregates disappeared and the TCPP molecules exist in the form of J-dimers again. These results are similar to the behaviors in acidic TCPP solutions [ 44 ]. The TCPP molecules in the core of PIC micelles exist in the form of H-aggregates at a ratio < 1:4, but still exist in the form of J-dimers at a ratio > 1:4.…”
Section: Resultssupporting
confidence: 87%
“…From this phenomenon, it can be inferred that H-aggregates disappeared and the TCPP molecules exist in the form of J-dimers again. These results are similar to the behaviors in acidic TCPP solutions [ 44 ]. The TCPP molecules in the core of PIC micelles exist in the form of H-aggregates at a ratio < 1:4, but still exist in the form of J-dimers at a ratio > 1:4.…”
Section: Resultssupporting
confidence: 87%
“…The most common approach aimed at improving porphyrin solubility in water is the synthesis of positively or negatively charged di-, tri-, or tetra-substituted derivatives, e.g., tetratolylporphyrin substituted by pyridinium groups [23,24]. Even though the positive charge is preferable because it secures the attractive interaction with negatively charged DNA, the negatively charged 5,10,15,20-tetrakis-(4-sulfonatophenyl)porphyrin (TPPS) has been also synthesized and amply studied [1,2,25]. Recently, various porphyrin-containing systems have been designed and tested [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Gröhn and coworkers studied the electrostatic association of porphyrins with oppositely charged polyelectrolytes and described several different structures depending on the chain architecture and stiffness [30,31]. An interesting paper was published by Zhao et al [25]. The authors studied the co-micellization of poly(4-vinyl pyridine)-b-poly(ethylene oxide) (P4VP-PEO) and poly(2-(dimethylamino)ethyl methacrylate)-b-poly(N-isopropylacrylamide) (PDMAEMA-PNIPAM) with TPPS in aqueous media and found that the hydrophobic π-π interaction of pyridine cycles with porphyrin plays an important role and contributes to the formation of associates at elevated pHs when PE chains are not ionized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porphyrins have received much attention because of their excellent spectroscopic, photophysical, photochemical, and assembly properties, such as high absorption coefficients and remarkable chemical stability. , Owing to their unique planar and rigid molecular geometry and easily modified periphery, porphyrins are widely utilized in supramolecular chemistry. Driven by noncovalent interactions such as π–π stacking, , hydrogen bonding, electrostatic interactions, and metal coordination, porphyrins can self-assemble into various nanostructures, enriching their photophysical and photochemical properties. …”
Section: Introductionmentioning
confidence: 99%